The main occupations of new farms in the Pishpek district of the Semirechensk region at the beginning of the 20th century (Journal of history, 2022)
The relevance of the study is due to the fact that this problem remains insufficiently studied in historiography.The purpose of the article is to reveal the economic development of the new villages of the Pishpek district of the Semirechensk region in the n. XX century based on the analysis of statistical and archival materials.The methodological basis for writing the article was the principles of historicism and objectivity using specific historical methods, including statistical analysis. The materials of resettlement statistics collected in the Pishpek district by a commission led by P.P. Rumyantsev, as well as the works of pre-revolutionary authors, were analyzed. The socio-economic structure of new farms in the Pishpek district is considered in detail, it is concluded that the farms that the Russian settlers were engaged in grain farming. The composition of crops on irrigated and non-irrigated lands was almost the same, the areas of crops sown on them were not the same. Cultivated crops were varied: rye, wheat, barley, millet, oats, sunflower, flax, hemp, potatoes, melons, alfalfa were sown. There was no proper crop rotation (winter – spring – fallow). Settlers were engaged in meat and dairy cattle breeding, horticulture, gardening. The economy was natural. The peasants were also engaged in crafts, they were handicraftsmen and small retailers, agricultural workers and farm laborers. Social stratification in new villages was just beginning. Key words: Semirechensk region, migrant peasants, new village farms, agriculture, cattle breeding, horticulture, beekeeping, crafts.